Subjective experiences of physical activity and forecasting bias during behavioral weight loss. (7th October 2021) - Crane, Nicole T.; Martinelli, Mary K.; Forman, Evan M.; Butryn, Meghan L.
Abstract: Introduction: Engagement in physical activity (PA) is a critical component of behavioral weight loss (BWL) treatment. Subjective experiences surrounding PA may shape exercise decisions and need to be further understood within a BWL sample. Methods: Participants in this study were adults with overweight/obesity enrolled in an 18‐month BWL program. At baseline, six, and 18 months, participants ( N = 320) predicted how they would feel during a lab‐based walking task and rated their experiences mid‐walk and post‐walk. They also completed self‐report questionnaires assessing depressive symptoms and discomfort intolerance. Results and Discussion: Results indicated that exercise experience and expectations were more positive at later treatment points than at baseline. At each assessment point, post‐walk ratings were more positive than mid‐walk ratings, but pre‐walk ratings did not differ from mid‐walk ratings, suggesting BWL participants were relatively accurate in predicting their PA experience. These results suggest treatment‐seeking adults with overweight/obesity feel most positive upon completion of PA, may not experience a forecasting bias as hypothesized and seem to have increasingly positive PA expectations and experiences as they proceed through treatment and lose weight. Lower discomfort intolerance and depressive symptoms were associated with more positive PA expectations and experiences. Understanding these individual differences in PA experience can inform intervention strategies.